Toxicological aspects of flavonoid interaction with biomacromolecules - Hodek, Petr; Hanustiak, Pavel; Krízková, Jitka; Mikelova, Radka; Krízková, Sona; Stiborová, Marie; Trnková, Libuse; Horna, Ales; Beklová, Miroslava; Kizek, René (Neuro endocrinology letters, 2006)
OBJECTIVES: Flavonoids are widely accepted as health promoting phytochemicals, however, some flavonoids show ability of direct interaction with DNA and/or enhance carcinogen activation into DNA modifying agents. Thus, their potential harmful effect on the human body should be examined in detail. METHODS: Direct interaction of flavonoids (quercetin, rutin) with DNA was examined using square wave voltammetry on carbon paste electrode. Induction effect of selected flavonoids on content of cytochrome P450 1A1, carcinogens activating enzyme, in colon and liver microsomal samples of animals exposed to flavonoids was determined by Western blotting, using anti-cytochrome P450 1A1 specific antibody. RESULTS: Of the natural flavonoids tested, induction of CYP1A1 was elicited by the typical citrus flavonoid naringenin in the colon, as well as by flavone in the liver. Moreover, synthetic beta-naphthoflavone and naturally occurring chrysin, quercetin and diosmin induced CYP1A1 in both tissues. The oxidation signals of guanine and adenine in the DNA molecule were decreased in the presence of flavonoids. CONCLUSIONS: Although flavonoids are often considered to be safe because of their "plant origin", ingestion of flavonoids should be taken with caution. Enhanced expression of CYP1A1 in colon tissue might be responsible for increasing incidence of colorectal carcinoma in humans. Electrochemistry can be used to study the interactions of flavonoids and DNA.
Keywords: Colon; Microsomes, Liver; Cytochrome P-450 CYP1A1; kolon; DNA, Single-Stranded; jednovláknová DNA; Male; Rats; jaterní mikrozomy; biologické modely; cytochrom P-450 CYP1A1; Enzyme Activation; Models, Biological; Flavonoids; Adenine; Animals; adenin; Guanidine; flavonoidy; guanidin; zvířata; mužské pohlaví; krysa rodu Rattus; aktivace enzymů; Electrochemistry; elektrochemie